Fair philosopher : Eliza Haywood and the female spectator - Wright, Lynn Marie; Newman, Donald J., 1947- (Bucknell studies in eighteenth-century literature and culture., 2006)
"Fair Philosopher, the first sustained scholarly study of The Female Spectator, brings together an impressive collection of established and upcoming Haywood scholars who challenge much of the received opinion about this groundbreaking journal. Several of the essays show that Haywood's periodical was far more political than is generally thought, that its connections to her career as a novelist are more intimate than has been recognized, and that The Spectator was a target as well as a model. This collection makes a convincing argument that Haywood's periodical deserves far more critical attention than it has received so far and suggests new lines of development for future Haywood scholarship."--Publisher's website.